Synthesis and Evaluation of Thermoresponsive Boron-Containing Poly(N-isopropylacrylamide) Diblock Copolymers for Self-Assembling Nanomicellar Boron Carriers - Yoneoka, Shuichiro (Polymers (Basel), 2018)
Development of new boron nanocarriers has been a crucial issue to be solved for advancing boron neutron capture therapy (BNCT) as an effective radiation treatment for cancers. The present study aimed to create a novel double-thermoresponsive boron-containing diblock copolymer based on poly(N-isopropylacrylamide) [poly(NIPAAm)], which exhibits two-step phase transitions (morphological transitions) at the temperature region below human body temperature. The boronated diblock copolymer considerably concentrates boron atoms into the water-dispersible (i.e., intravenous-administration possible) nanomicelles self-assembled by the first phase transition, and furthermore the properly controlled size and hydrophobicity of the second phase-transitioned nanoparticles are expected to make a significant contribution to the selective delivery and long-term retention of boron atoms into tumor tissues. Here we present the detailed synthesis of the strategic NIPAAm-based diblock copolymer with 3-acrylamidophenylboronic acid (PBA), i.e., poly(NIPAAm-block-NIPAAm-co-PBA), through a reversible addition-fragmentation chain transfer polymerization. Furthermore, the stepwise phase transition behavior of the obtained boronic-acid diblock copolymers was characterized in detail by temperature-variable (1)H and (11)B-nuclear magnetic resonance spectroscopy. The phase-transition-induced molecular structural changes, including the structural compositions and sizes of nanomicelles and nanoparticles, are also discussed here.